+0  
 
+1
61
1
avatar

Thank you in advance.

 Dec 20, 2019

Best Answer 

 #1
avatar+19789 
0

Remember  log (a/b) = log a - log b  

    and  log (ab) = log a + log b

So:

 

Log7x + logy - log7z=  log7 (xy/z)

 

 

e4/3ln2-1 =  e4/3ln2 (e-1) = eln2^4/3 /e   = 2(4/3)/e = \(\sqrt[3]{2^4}\)   / e =  2\(\sqrt[3]{2}\) / e

 

 

You should be able to see their errors.....

 Dec 20, 2019
edited by ElectricPavlov  Dec 20, 2019
 #1
avatar+19789 
0
Best Answer

Remember  log (a/b) = log a - log b  

    and  log (ab) = log a + log b

So:

 

Log7x + logy - log7z=  log7 (xy/z)

 

 

e4/3ln2-1 =  e4/3ln2 (e-1) = eln2^4/3 /e   = 2(4/3)/e = \(\sqrt[3]{2^4}\)   / e =  2\(\sqrt[3]{2}\) / e

 

 

You should be able to see their errors.....

ElectricPavlov Dec 20, 2019
edited by ElectricPavlov  Dec 20, 2019

6 Online Users

avatar